2019
DOI: 10.1111/tpj.14443
|View full text |Cite
|
Sign up to set email alerts
|

Affinity‐based high‐resolution analysis of DNA binding by VASCULAR‐RELATED NAC‐DOMAIN7 via fluorescence correlation spectroscopy

Abstract: VASCULAR-RELATED NAC-DOMAIN7 (VND7) is the master transcription factor for vessel element differentiation in Arabidopsis thaliana. To identify the cis-acting sequence(s) bound by VND7, we employed fluorescence correlation spectroscopy (FCS) to find VND7-DNA interactions quantitatively. This identified an 18-bp sequence from the promoter of XYLEM CYSTEINE PEPTIDASE1 (XCP1), a direct target of VND7. A quantitative assay for binding affinity between VND7 and the 18-bp sequence revealed the core nucleotides contri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 61 publications
0
8
0
Order By: Relevance
“…Only VND7 could bind to the NbXCP1 promoter (Supplemental Figure S4, Figure 4C). The target sequence of VND7 (Tamura et al, 2019) was identified in the NbXCP1 promoter (Figure 4C). An equivalent sequence was present in the NbXCP2 promoter, although it contained a mismatch of one terminal nucleotide.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Only VND7 could bind to the NbXCP1 promoter (Supplemental Figure S4, Figure 4C). The target sequence of VND7 (Tamura et al, 2019) was identified in the NbXCP1 promoter (Figure 4C). An equivalent sequence was present in the NbXCP2 promoter, although it contained a mismatch of one terminal nucleotide.…”
Section: Resultsmentioning
confidence: 99%
“…XYN1 was verified expression on the predominantly in xylem tissues and encodes xylanase. The xylem transport patterns were affected in AtXYN1 modified lines (Zeilinger et al, 1996;Suzuki et al, 2002;Endo et al, 2019). In the module of xylem formation, genes associated with the generation and scavenging of reactive oxygen species (ROS) were found (Figure 3, Supplemental Table S7).…”
Section: Discussionmentioning
confidence: 99%
“…The results showed that the motifs in the diploids and autotetraploids were different. However, the binding motifs in both diploid and autotetraploid sour jujube have a continuous core sequence, CTTNAAG, which is conserved with core sequence published by Tamura et al (2019).…”
Section: Genome-wide Identification Of the Direct Downstream Targets ...mentioning
confidence: 99%
“…Putative target genes of VND have been reported in A. thaliana (Tamura et al, 2019), maize (Dong et al, 2020), and poplar (Ohtani et al, 2011). These target genes were predicted to be related to the regulation of xylem development, programmed cell death, cell wall synthesis, metabolic enzymes, and signal transduction.…”
Section: Differential Expression Of Genes Related To Zjvnd7 Putative ...mentioning
confidence: 99%
“…Dynamic parameters of the fluorescently labeled molecules can be discerned by fitting the autocorrelation curve with a suitable model function . In contrast to smFRET measurements, smFCS is not limited to a detection size of 1–10 nm and is sensitive to distances shorter than 1 nm, , making it applicable to a wide range of investigations in the biological sciences such as obtaining reaction rates, diffusion coefficients, and affinity constants. …”
Section: Labeled Single-molecule Nanotechnologiesmentioning
confidence: 99%